Metode Pembelajaran PKN SD Al-Wasliyah 11 Amplas - Abdulgani Jamora Nasution; Adelia Priscila Ritonga; Devi Intan Sari Sagala; Sa’idatul Hasanah (EduInovasi: Journal of Basic Educational Studies, 2023)
The background of this research is the efforts of researchers to describe the implementation of the PPKN learning method at SD al-washliyah 11 Amplas. The learning method is a component of education that is very influential on the success of teachers in achieving educational goals. The use of one type of method tends to produce teaching and learning activities that are boring for students, the learning process will feel stiff and students are less enthusiastic about learning. The teacher has implemented lecture and example non-example learning methods but these methods are still considered lacking and very boring for students. The purpose of this research was carried out at SD al-Washliyah 11 Amplas to find out the implementation of PPKN learning methods and innovative learning methods suggested by teachers and school principals. This type of research uses qualitative research methods to determine how to find, collect, process and analyze the research data. The conclusion from the results of the PPKN learning method research, with the innovation of the CTL learning method students become more active in learning. It is hoped that this research will become information material and input for teaching and learning activities in schools, especially at Al-Washliyah 11 Amplas Elementary School, especially in giving encouragement to students to always increase their interest in learning to achieve more adequately. Keywords: Learning Methods, CTL, Lectures, example non example.